The influence of local government competition on residents’ perceptions of social fairness—Evidence from China - Yi, Junling; Li, Jingling (Frontiers in Psychology, 2022)
Social fairness has been one of the important issues and pursuits in the course of human history since ancient times, and the promotion of social fairness has become a social consensus. Based on the data from the years 2013, 2015, and 2017 Chinese General Social Survey (CGSS), an ordered probit model was constructed for empirical testing to explore the effect of local government competition on residents’ perceptions of social fairness and its internal mechanism. The research results show that: (1) Local government competition expands residents’ perceptions of social unfairness. (2) Local government competition increases residents’ perceptions of social unfairness through the paths of increasing residents’ income disparity, crowding out the supply of basic government public goods, and increasing corruption. (3) Local government competition has a significant negative effect on the perceptions of social fairness of the middle-income as well as the high-income but does not affect the low-income. The inhibitory effect of local government competition on the perceptions of social fairness of residents in urban as well as eastern regions is more significant than that in rural and central and western regions. This study has important practical implications for promoting common prosperity to build a harmonious, fair, and democratic modern welfare state and improving the governance capacity of local governments.